2022
DOI: 10.1177/13623613221106400
|View full text |Cite
|
Sign up to set email alerts
|

Clinician factors related to the delivery of psychotherapy for autistic youth and youth with attention-deficit hyperactivity disorder

Abstract: Autistic children and adolescents are more likely than non-autistic youth to experience mental health problems, such as anxiety or depression, but less likely to receive psychotherapy to address these concerns. Recent research indicates that clinician factors, such as knowledge, attitudes, confidence and beliefs, can impact their decisions to provide care, though this work has primarily focused on adults or within the context of one kind of treatment (cognitive behaviour therapy). The current study examined ps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 59 publications
(87 reference statements)
0
1
0
Order By: Relevance
“…Behavior change theories indicate that the level of knowledge impacts the use and adoption of EBTs ( Higa & Chorpita, 2008 ). Roudbarani et al (2022) recently found that clinician knowledge of mental health-related topics (e.g., symptoms of mental health disorders and treatment plan development) predicted the clinician's intentions to use an EBT with children diagnosed with developmental disorders. Other research highlights that EBT knowledge may not necessarily influence their attitude toward or use of an EBT ( Nakamura et al, 2011 ; Walrath et al, 2006 ).…”
Section: Introductionmentioning
confidence: 99%
“…Behavior change theories indicate that the level of knowledge impacts the use and adoption of EBTs ( Higa & Chorpita, 2008 ). Roudbarani et al (2022) recently found that clinician knowledge of mental health-related topics (e.g., symptoms of mental health disorders and treatment plan development) predicted the clinician's intentions to use an EBT with children diagnosed with developmental disorders. Other research highlights that EBT knowledge may not necessarily influence their attitude toward or use of an EBT ( Nakamura et al, 2011 ; Walrath et al, 2006 ).…”
Section: Introductionmentioning
confidence: 99%